Bioblock technique to treat severe internal resorption with subsequent periapical pathology: a case report - Márk Fráter; Tekla Sáry; Sufyan Garoushi (Korea, Republic of (South Korea), 2022)
A variety of therapeutic modalities can be used for the endodontic treatment of a traumatized tooth with internal root resorption (IRR). The authors present a case report of the successful restoration of a traumatized upper central incisor that was weakened due to severe IRR and subsequent periapical lesion formation. A 20-year-old female patient was referred to our clinic with severe internal resorption and subsequent periapical pathosis destroying the buccal bone wall. Root canal treatment had been initiated previously at another dental practice, but at that time, the patient's condition could not be managed even with several treatments. After cone-beam computed tomography imaging and proper chemomechanical cleaning, the tooth was managed with a mineral trioxide aggregate plug followed by root canal filling using short fiber-reinforced composite, known as the Bioblock technique. This report is the first documentation of the use of the Bioblock technique in the restoration of a traumatized tooth. The Bioblock technique appears to be ideal for restoring wide irregular root canals, as in cases of severe internal resorption, because it can uniquely fill out the hollow irregularities of the canal. However, further long-term clinical investigations are required to provide additional information about this new technique.